Studi Banding Sifat Ketahanan Struktural Terhadap Kekeringan Antara Varietas Padi Sawah Dan Padi Gogo Berdasarkan Struktur Anatomi Daun - Witiyasti Imaningsih (Bioscientiae, 2006)
Experimental study has been conducted (1) to find out the structural droughtresistance traits of “Sawah” rice and “Gogo” rice , and (2) to determine the difference in leaf structure among  some Sawah rice and Gogo rice varieties. Randomly chosen samples were taken, and slides were prepared using paraffin method. Structural traits of the roots and leaves were observed: anatomical structure leaves, leaf thickness, leaf cuticle thickness, number of stomata per leaf square unit, number of trichome per leaf square unit, and number of motor cell per row.The results showed that Sawah rice and Gogo rice differed in their structural droughtresistance.